The Role of Profitability, Company Size, Capital Structure, and Liquidity Risk on Firm Value of Indonesian Banks - Fenty Fauziah; Rafiqoh Rafiqoh (Universitas Winaya Mukti, 2021)
The main objective of any firm is to maximize shareholder's wealth, which can be seen from firm value. This study aims to analyze and explain the effect of profitability, company size, capital structure, and liquidity risk on firm value banking companies in Indonesia. The population of this study is all banking companies listed on the Indonesia Stock Exchange, with an observation period of 2017-2018. The sample selection using a purposive sampling method. Data have both cross-section and time variation. Analysis and hypothesis testing were carried out by using a linear regression analysis using Eviews 11. The results showed that investors viewed that the company's overall profits from its business activities could increase its share price. The capital structure owned by the public relatively small, which meant that the company could provide a source of funds from within the company in the form of the owner's capital or retained earnings. Funds obtained from loans, if they were not followed by the ability to manage funds or were not channeled back to the community, would cause interest expenses and destroy profits. This condition results in investors selling their shares. Investors in making investment decisions paid attention to one indicator at a time and paid attention to all the factors that determined the company's value.